2021
DOI: 10.1001/jamanetworkopen.2021.22559
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of a Multicomponent Intervention for Hypertension Control in Low-Income Settings in Argentina

Abstract: IMPORTANCE Hypertension is highly prevalent in low-and middle-income countries, and it is an important preventable risk factor for cardiovascular diseases (CVDs). Understanding the economic benefits of a hypertension control program is valuable to decision-makers.OBJECTIVE To evaluate the long-term cost-effectiveness of a multicomponent hypertension management program compared with usual care among patients with hypertension receiving care in public clinics in Argentina from a health care system perspective. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 33 publications
0
16
0
1
Order By: Relevance
“…1 . From 3056 studies (2503 after duplicate removal) identified through database searches, 14 studies evaluated the value for money of either website 26 30 , text-messaging 27 , 31 36 , or smartphone application interventions 29 , 37 39 . An overview of study characteristics, intervention details, and health economic outcomes can be found in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 . From 3056 studies (2503 after duplicate removal) identified through database searches, 14 studies evaluated the value for money of either website 26 30 , text-messaging 27 , 31 36 , or smartphone application interventions 29 , 37 39 . An overview of study characteristics, intervention details, and health economic outcomes can be found in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Supplementary note 1 shows excluded studies at full text screening with reasons. Augustovski et al 31 and Zhang et al 36 reported on the same trial but the former was a trial-based analysis while the latter was model-based to extrapolate costs and effects on the long-term.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“… 55 The protective effects and cost‐effectiveness related to cardiovascular risks and stroke were sustained long‐term. 56 Multinational collaboration and coordinated efforts are needed to implement similar programs in primary care systems across LACs.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the heterogeneity in the willingness to pay among health subsectors of Argentina and the lack of a specific explicit cost-effectiveness threshold, the decision rule to define the cost-effectiveness threshold was assessed within a range going from one (ARS $ 700,473) to five (ARS $ 3,502,363) gross domestic product (GDP) per-capita per QALY gained. The range of the decision rule was defined based on previous economic evaluations published in Argentina [28][29][30][31][32] and the willingness-to-pay threshold of 5 GDP was explored, since the indication for a centrifugal-flow pump is recommended for end-of-life care in the case of a disease associated with short life expectancy that would be extended thanks to the device. The consideration of a higher willingness-to-pay has been contemplated by the National Institute for Health and Care Excellence (NICE) in the United Kingdom upon establishing the criteria for the appraisal of end-of-life treatments [33], and has been used in a recent study in Argentina [30].…”
Section: Decision Modelmentioning
confidence: 99%